Fragment-based lead discovery of a novel class of small molecule antagonists of neuropeptide B/W receptor subtype 1 (GPR7). Issue 23 (1st December 2020) - Moningka, Remond; Romero, F. Anthony; Hastings, Nicholas B.; Guo, Zhiqiang; Wang, Ming; Di Salvo, Jerry; Li, Ying; Trusca, Dorina; Deng, Qiaoling; Tong, Vincent; Terebetski, Jenna L.; Ball, Richard G.; et al.
Graphical abstract: Abstract: Here, we report the discovery of a new class of NPBWR1 antagonists identified from a fragment-based screen. Compound 1 (cAMP IC50 = 250 µM; LE = 0.29) emerged as an initial hit. Further optimization of 1 by SAR-by-catalogue and chemical modification produced 21a (cAMP IC50 = 30 nM; LE = 0.39) with a 6700-fold increase in potency from fragment 1 . Somewhat surprisingly, Schild analysis of compound 21a suggested that in vitro inhibition of NPW-mediated effects on upon cAMP accumulation were saturable, and that compound 21a dose-dependently increased [125I]-hNPW23 dissociation rate constants from NPBWR1 in kinetic binding studies. Collectively, these data are inconsistent with a classic surmountable, orthosteric mechanism of inhibition. The benzimidazole inhibitors reported herein may therefore represent a mechanistically differentiated class of compounds with which to form a better appreciation of the pharmacology and physiological roles of this central neuropeptide system.